Sarcosaprophagous Diptera assemblages in natural habitats in central Spain: spatial and seasonal changes in composition - MARTÍN-VEGA, D; Baz, A (Medical and Veterinary Entomology, 2012)
The composition and spatial distribution of sarcosaprophagous Diptera assemblages were studied using carrion-baited traps along a bioclimatic gradient of natural habitats in central Spain throughout the different seasons during 1 year. Calliphoridae and Muscidae were the most abundant families, accounting for, respectively, 41.9% and 35.1% of all Diptera specimens collected. Other abundant families were Heleomyzidae (8.4%), Sarcophagidae (6.9%) and Piophilidae (5.1%). Fly assemblage compositions differed among bioclimatic levels, with Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) being the dominant species in mesomediterranean habitats, Muscina levida (Harris) (Diptera: Muscidae) the dominant species in supramediterranean habitats, and Prochyliza nigrimana (Meigen) (Diptera: Piophilidae) the dominant species in oromediterranean habitats. Differences in assemblage composition were also found among seasons. Thermophobic species such as Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) and some species of Heleomyzidae were well represented during autumn, winter and spring in the three bioclimatic levels sampled. By contrast, thermophilic species such as Ch. albiceps and Lucilia sericata (Meigen) (Diptera: Calliphoridae) and most Muscidae and Sarcophagidae species were more abundant during summer and in mesomediterranean habitats located at lower elevations. Knowledge of the preferences of some species for certain habitats may be of ecological and forensic value and may establish a starting point for further research.
Keywords: Animals; Biota; climate; Diptera; Diptera: classification; Diptera: physiology; Ecosystem; Forensic entomology; habitat association; sarcosaprophagous Diptera; Seasons; Spain

Actividad espacio-temporal de Polietes meridionalis Peris & Llórente , 1963 ( Díptera : Muscidae ) en un ecosistema de encinar * - Rojo, S; Marcos-garcía, M A (Boletín de Sanidad Vegetal Plagas, 1995)
Some aspects of the biology of Polietes meridionalis Peris & Llórente 63 have been analysed in a holm-oak ecosystem (dehesa) located in the Tberian Mediterranean área. The specimens were caught with pit-fall traps baited with cattle dung, placed according to habitat gradient. They were collected at dífferent hourly periods to fix a distribution model in space and time and its variation during the year.
Keywords: coprophagous diptera; Diptera; holm-oak; Muscidae; Polietes meridionalis; space-temporal distribution

Colonisation d'un nouvel habitat par Culex pipiens (Diptera, Culicidae) : le creux d'arbre des subéraies en pays Zaer, Maroc - Metge, G; Belakoul, N (Annales de Limnologie - International Journal of Limnology, 1989)
The dry conditions which occurred in Morocco from 1981 to 1983 have resulted in the selection of a new habitat by Culex pipiens, which is a very adaptable species, in hollows of trees. Morphological descriptions of the fourth larval instar, the pupae and the male and female adults have shown that these populations living in iree holes (phytotelmata) belong to the form C. pipiens autogenicus.
Keywords: Culex pipiens; Culicidae; Diptera; ecology; habitat; Morocco; taxonomy